Mass measurements of neutron-rich indium isotopes for r-process studies - Izzo, Christopher; Bergmann, Julian; Dietrich, Kilian; Dunling, Eleanor; Fusco, Domenico; Jacobs, A.; Kootte, Brian; Kripkó-Koncz, Gabriella; Lan, Y.; Leistenschneider, E.; Lykiardopoulou, Eleni Marina; Mukul, Ish; et al. (Physical review, 2021)
A new series of neutron-rich indium mass measurements is reported from the TITAN multiple-reflection time-of-flight mass spectrometer (MR-TOF-MS). These mass measurements cover 125−134In (N=76–85) and include ground states as well as isomeric states. The masses of nuclei in this region are known to be of great importance for accurately modeling r-process nucleosynthesis, and the significance of the reported neutron-rich indium masses is discussed in this context. Results are compared with earlier experimental data where available as well as theoretical mass models. The measurements reported here include the first mass measurements of 133,134In, as well as the first direct mass measurement of 132In. The masses of 125−131In ground states and several isomers were previously measured to higher precision by Penning trap mass spectrometry, which also resolved some low-lying isomers that could not be resolved in this work. The earlier Penning trap measurements serve as excellent cross-checks for the MR-TOF-MS measurements, and in some cases the MR-TOF-MS measurements improve the literature uncertainties of higher-lying isomer masses and excitation energies. A new isomeric state for 128In, recently reported for the first time by the JYFLTRAP group, is also confirmed by the TITAN MR-TOF-MS, with a measured excitation energy of 1813(17) keV.
Gesehen am 13.12.2021